What Does "Good Adjustment" Mean for Chinese International Students? A Qualitative Investigation. (November 2018) - Lu, Yun; Chui, Harold; Zhu, Runsheng; Zhao, Hongyang; Zhang, Yangyang; Liao, Jie; Miller, Matthew J.
In this study, we aimed to provide a rich description of Chinese graduate international students' ways of coping with adjustment challenges and their subjective appraisal of adjustment. Nine Chinese graduate international students (six women, three men) from different institutions and disciplines reported their perceptions of the broad sociopolitical context, cultural adjustment experiences, and subjective evaluation of adjustment. We analyzed the data using consensual qualitative research method. Findings were summarized into three domains: (a) Perceived Sociopolitical Context, (b) Cultural Adjustment Challenges, and (c) Coping and Adjustment. We found frequent long-standing challenges in social and professional domains. Furthermore, interviewees reported an ongoing evaluative process where they negotiated host culture participation expectations in the context of adjustment challenges to achieve a subjective sense of satisfaction. Our findings have implications for professionals working with Chinese international students to help them mitigate internalized oppression and develop purpose and well-being.